CRISPR–Cas systems and applications for crop bioengineering - Uranga, Mireia; Martín-Hernández, Ana Montserrat; De Storme, Nico; Pasin, Fabio (Frontiers in Bioengineering and Biotechnology, 2024)
CRISPR–Cas technologies contribute to enhancing our understanding of plant gene functions, and to the precise breeding of crop traits. Here, we review the latest progress in plant genome editing, focusing on emerging CRISPR–Cas systems, DNA-free delivery methods, and advanced editing approaches. By illustrating CRISPR–Cas applications for improving crop performance and food quality, we highlight the potential of genome-edited crops to contribute to sustainable agriculture and food security.